2015
DOI: 10.1016/j.nbd.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

PARK2 patient neuroprogenitors show increased mitochondrial sensitivity to copper

Abstract: Poorly-defined interactions between environmental and genetic risk factors underlie Parkinson’s disease (PD) etiology. Here we tested the hypothesis that human stem cell derived forebrain neuroprogenitors from patients with known familial risk for early onset PD will exhibit enhanced sensitivity to PD environmental risk factors compared to healthy control subjects without a family history of PD. Two male siblings (SM and PM) with biallelic loss-of-function mutations in PARK2 were identified. Human induced plur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…S1a and S1b). [19, 23] The absence of episomal vector genomic integration was confirmed by PCR (data not shown). Immunostaining for pluripotency markers used the following antibodies; OCT4 (mouse monoclonal, Millipore), NANOG (affinity purified anti-goat IgG), and SSEA4 (rabbit monoclonal, Millipore) (Fig.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…S1a and S1b). [19, 23] The absence of episomal vector genomic integration was confirmed by PCR (data not shown). Immunostaining for pluripotency markers used the following antibodies; OCT4 (mouse monoclonal, Millipore), NANOG (affinity purified anti-goat IgG), and SSEA4 (rabbit monoclonal, Millipore) (Fig.…”
Section: Methodsmentioning
confidence: 84%
“…S2a). [1921] Direct differentiation of these iPSCs cultured on Matrigel, outlined in Fig. S2b, successfully yielded iPSC-CMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, a number of epidemiological and clinical studies have suggested potential environmental risk factors for PD, including environmental exposure to certain pesticides and fungicides such as paraquat, rotenone and maneb, and some surrogate factors such as living in rural areas, drinking well water and farming. In addition, exposure to heavy metals such as iron, lead, mercury, cadmium, arsenic and manganese, as well as to metal-based nanoparticles, has also been shown to increase the risk of PD through the accumulation of metals in the mid brain and increased oxidative stress-mediated apoptosis (Aboud, et al, 2014; Afeseh Ngwa, et al, 2009; Afeseh Ngwa, et al, 2011; Harischandra, Jin, Anantharam, Kanthasamy, & Kanthasamy, 2015; Kanthasamy, et al, 2012; Milatovic, Zaja-Milatovic, Gupta, Yu, & Aschner, 2009). Currently, the effect of environmental factors on the host gut microbiome is completely unknown.…”
Section: The Gut Microbiomementioning
confidence: 99%
“…The study concludes that this synergism induces cell death via the perturbation of the ubiquitin-proteasome and autophagic systems, albeit independently from protein aggregation. The study from Aboud et al (2014) explores the synergism between complete loss-of-function of parkin caused by homozygous mutations in the PARK2 gene and exposure to metals. The rationale of the approach stems from the incomplete penetrance of PARK2 loss-of-function mutations, which causes high intra-familial and inter-familial variability in ages of onset, and therefore reinforces the role of environmental exposure in eliciting pathogenesis.…”
mentioning
confidence: 99%